CompTIA A+ guide to IT technical support - Andrews, Jean 1946-; Dark, Joy; West, Jill (CompTIA A+, 2017)
This step-by-step, highly visual text provides a comprehensive introduction to managing and maintaining computer hardware and software. Written by best-selling author and educator Jean Andrews, A+ Guide to IT Technical Support, 9th Edition closely integrates the CompTIA+ Exam objectives to prepare you for the 220-901 and 220-902 certification exams. The new Ninth Edition also features extensive updates to reflect current technology, techniques, and industry standards in the dynamic, fast-paced field of PC repair and information technology. Each chapter covers both core concepts and advanced topics, organizing material to facilitate practical application and encourage you to learn by doing. The new edition features more coverage of updated hardware, security, virtualization, new coverage of cloud computing, Linux and Mac OS, and increased emphasis on mobile devices. Supported by a wide range of supplemental resources to enhance learning with Lab Manuals, CourseNotes online labs and the optional MindTap that includes online labs, certification test prep and interactive exercises and activities, this proven text offers students an ideal way to prepare for success as a professional IT support technician and administrator.